WISDOM Project – XVII. Beam-by-beam properties of the molecular gas in early-type galaxies - Williams, TG; Liang, F-H; Bureau, MG; Davis, TA; Cappellari, M; Choi, W; Elford, JS; Iguchi, S; Gensior, J; Lu, A; Ruffa, I; Zhang, H (Oxford University Press, 2023)
We present a study of the molecular gas of seven early-type galaxies with high angular resolution data obtained as part of the mm-Wave Interferometric Survey of Dark Object Masses (WISDOM) project with the Atacama Large Millimeter/submillimeter Array. Using a fixed spatial-scale approach, we study the mass surface density (Σ) and velocity dispersion (σ) of the molecular gas on spatial scales ranging from 60 to 120 pc. Given the spatial resolution of our data (20–70 pc), we characterize these properties across many thousands of individual sightlines (≈50 000 at our highest physical resolution). The molecular gas along these sightlines has a large range (≈2 dex) of mass surface densities and velocity dispersions ≈40 per cent higher than those of star-forming spiral galaxies. It has virial parameters αvir that depend weakly on the physical scale observed, likely due to beam smearing of the bulk galactic rotation, and is generally supervirial. Comparing the internal turbulent pressure (Pturb) to the pressure required for dynamic equilibrium (PDE), the ratio Pturb/PDE is significantly less than unity in all galaxies, indicating that the gas is not in dynamic equilibrium and is strongly compressed, in apparent contradiction to the virial parameters. This may be due to our neglect of shear and tidal forces, and/or the combination of three-dimensional and vertical diagnostics. Both αvir and Pturb anticorrelate with the global star-formation rate of our galaxies. We therefore conclude that the molecular gas in early-type galaxies is likely unbound, and that large-scale dynamics likely plays a critical role in its regulation. This contrasts to the giant molecular clouds in the discs of late-type galaxies, that are much closer to dynamical equilibrium.